Assembling Embodiment: Body, Techniques and Things - Murphy, Stephen (My University, 2020)
The sensory turn in CCT illuminates the sensuous, affective and skilful nature of embodied consumption experiences. To date however, little is known about how material things feature in the constitution of embodiment. This paper extends assemblage theory to examine the physical and mindful cultivation of skilled embodiment in socio-material relations.
PUBLISHED
Keywords: Creative Technologies; Identities in Transformation